Shape-Memory Polymers - Lendlein, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
-Shape-Memory Polymers and Shape-Changing Polymers By M. Behl, J. Zotzmann, and A. Lendlein -Shape-Memory Polymer Composites By Samy A. Madbouly and Andreas Lendlein -Characterization Methods for Shape-Memory Polymers By W. Wagermaier, K. Kratz, M. Heuchel, and A. Lendlein -Shape-Memory Polymers for Biomedical Applications By Christopher M. Yakacki and Ken Gall -Controlled Drug Release from Biodegradable Shape-Memory Polymers By ChristianWischke, Axel T. Neffe, and Andreas Lendlein
Shape-Memory Polymers and Shape-Changing Polymers -- Shape-Memory Polymer Composites -- Characterization Methods for Shape-Memory Polymers -- Shape-Memory Polymers for Biomedical Applications -- Controlled Drug Release from Biodegradable Shape-Memory Polymers.
Keywords: Chemistry; Polymers; Biochemistry; Pharmacy; Chemistry; Polymer Sciences; Medicinal Chemistry; Pharmacy; Biochemistry, general